Deciphering the Peculiar Behavior of β-Lapachone in Lipid Monolayers and Bilayers - Wu, Xiao (Langmuir : the ACS journal of surfaces and colloids, 2019)
β-Lapachone (β-Lap) is a promising anticancer drug whose applications have been limited so far because of its poor solubility and stability. Its encapsulation in liposomes has been proposed to overcome these issues. However, surface pressure measurements show that β-Lap exhibits atypical interfacial behavior when mixed with lipids. Although the drug does not seem to be retained in lipid monolayers as deduced from the π-A isotherms, small changes in compressibility moduli suggest that β-Lap actually interacts with lipids, either disorganizing or rigidifying their monolayers. Thermal and structural analyses of lipid bilayers confirm the existence of β-Lap/lipid interactions and show that the drug inserts between hydrophobic chains, close to the polar headgroup in DPPC bilayers and deeper in the acyl chains in POPC bilayers. Molecular dynamics simulations allow a comprehensive description of the drug position and orientation in DOPC and POPC bilayers in the presence or absence of cholesterol